Contractile properties are disrupted in Becker muscular dystrophy, but not in limb girdle type 2I. Issue 3 (10th August 2016) - Løkken, Nicoline; Hedermann, Gitte; Thomsen, Carsten; Vissing, John
Abstract : We investigated whether a linear relationship between muscle strength and cross‐sectional area (CSA) is preserved in calf muscles of patients with Becker muscular dystrophy (BMD, n = 14) and limb‐girdle type 2I muscular dystrophy (LGMD2I, n = 11), before and after correcting for muscle fat infiltration. The Dixon magnetic resonance imaging technique was used to quantify fat and calculate a fat‐free contractile CSA. Strength was assessed by dynamometry. Muscle strength/CSA relationships were significantly lower in patients versus controls. The strength/contractile‐CSA relationship was still severely lowered in BMD, but was almost normalized in LGMD2I. Our findings suggest close to intact contractile properties in LGMD2I, which are severely disrupted in BMD. Ann Neurol 2016;80:466–471